An in vitro model of Fusobacterium nucleatum and Porphyromonas gingivalis in single-and dual-species biofilms - Tavares, Lívia Jacovassi [UNESP]; Klein, Marlise Inêz [UNESP]; Panariello, Beatriz Helena Dias [UNESP]; de Avila, Erica Dorigatti [UNESP]; Pavarina, Ana Cláudia [UNESP] (XMLink, 2018)
Purpose: The goal of this study was to develop and validate a standardized in vitro pathogenic biofilm attached onto saliva-coated surfaces. Methods: Fusobacterium nucleatum (F. nucleatum) and Porphyromonas gingivalis (P. gingivalis) strains were grown under anaerobic conditions as single species and in dual-species cultures. Initially, the bacterial biomass was evaluated at 24 and 48 hours to determine the optimal timing for the adhesion phase onto saliva-coated polystyrene surfaces. Thereafter, biofilm development was assessed over time by crystal violet staining and scanning electron microscopy. Results: The data showed no significant difference in the overall biomass after 48 hours for P. gingivalis in single- and dual-species conditions. After adhesion, P. gingivalis in single- and dual-species biofilms accumulated a substantially higher biomass after 7 days of incubation than after 3 days, but no significant difference was found between 5 and 7 days. Although the biomass of the F. nucleatum biofilm was higher at 3 days, no difference was found at 3, 5, or 7 days of incubation. Conclusions: Polystyrene substrates from well plates work as a standard surface and provide reproducible results for in vitro biofilm models. Our biofilm model could serve as a reference point for studies investigating biofilms on different surfaces.
Keywords: Bacterial adhesion; Biofilms; Fusobacterium nucleatum; Porphyromonas gingivalis